Enhancing bauxite residue properties for plant growth: Gypsum and organic amendment effects on chemical properties of soil and leachate - Miura, Yuuki Silveira; Mulder, Jan; Zivanovic, Valentina; Courtney, Ronan; Okkenhaug, Gudny (Journal of environmental management, 2023)
Here, we assess the effects of gypsum and local organic waste as amendments to non-weathered, filter-pressed bauxite residue (BR) to improve its properties and support plant growth. In addition, we monitored the leachate quality of the amended BR under progressive leaching that simulated precipitation conditions in Northern Brazil. Free-draining column tests consisting of BR amended with gypsum and organic waste, at 5% and 10% w/w, respectively, were leached for 8 weeks to assess the effects on the chemical composition of BR and the leachates. Adding gypsum to BR reduced the exchangeable sodium (Na) percentage (ESP) from approximately 79%–48%, whereas adding only organic waste had smaller effects on ESP (from ∼79% to ∼ 70%). The mean leachate pH ranged from 8.7 to 9.4 for the gypsum, and organic waste amended BR, while this was 10.3 in the leachate of the unamended BR. The treatments had similar trends of electrical conductivity throughout the experiments and were below 2 dS/cm after 8 weeks, when ∼1.700 mm simulated precipitation had leached. Aluminium (Al), Arsenic (As), and Vanadium (V) concentrations in leachates of BR with gypsum, either alone or in combination with organic waste, were significantly lowered than in leachate of non-amended BR. By contrast, metal concentrations increased if organic waste was added to BR. We conclude that amending BR with gypsum, in combination with organic waste, significantly improves the chemical properties of the solid phase and achieved rehabilitation goals for SAR and EC of the leachates after 8 weeks of leaching. However, despite high leaching rates, rehabilitation goals for pH and ESP were not achieved with gypsum either alone or combined with organic waste. [Display omitted] •Bauxite residue has physicochemical properties which are not suitable for plant growth.•Different remediation strategies were assessed in leaching column experiments.•Gypsum and organic waste promoted suitable physicochemical conditions for plant growth.•Al, As and V concentrations decreased substantially due to gypsum amendment.•Rehabilitation goals were hardly achieved in non-weathered bauxite residue.